Effects of different annual irrigation strategies on soil water, salt, nitrogen leaching, and sunflower growth in saline soils of arid regions - Jiawei Liu; Lei Sun; Xiaojiang Zhu; Huaxian Deng; Yiming Fan; Quanzhong Huang; Guanhua Huang (Agricultural Water Management)
In arid irrigation areas, rising soil salinization and low irrigation water-use efficiency are growing concerns. This study aimed to investigate the effects of various annual irrigation strategies on soil water, salt, and nitrogen leaching, and sunflower yield using double-ring infiltrometers. The experiment, conducted in 2022 and 2023, applied five irrigation levels during presowing irrigation (PI1–PI5), sunflower growth irrigation (SI1–SI5), and autumn irrigation (AI1–AI5), with respective application ranges of 110–230, 60–140, and 120–240 mm. Presowing and autumn irrigation considerable increased soil water storage, while irrigation during the sunflower growth period primarily maintained soil water balance. Groundwater evaporation from May to October was 208 ± 27 mm in 2022 but decreased to 130 ± 17 mm in 2023 due to a considerable decline in groundwater levels. Presowing and autumn irrigation effectively reduced soil salinity and promoted uniform salt distribution within the soil profile. Over the 2-year period, the average desalinization rates at the 0–60 cm soil depth ranged from 20 % to 47 % during presowing irrigation, 3–12 % during sunflower growth irrigation, and 15–38 % during autumn irrigation. Excessive irrigation led to notable nitrogen loss and increased deep percolation, ultimately reducing crop yield and irrigation water productivity. Sunflower yield and irrigation water productivity under the PI3 + SI3 treatment reached 4.02 t ha−1 and 14.7 kg m−3, respectively. Based on a comprehensive evaluation using the EWM-TOPSIS-AISM model and the soil salt leaching coefficient during the nongrowth period, the recommended optimal irrigation strategy for border-irrigated sunflower fields on sandy loam in this area is a combination of PI-170 mm, SI-100 mm, and AI-164 mm.